The Factor of Self-Confidence Affecting to Indonesian Young Learners’ English Speaking Proficiency Level - Muhamad Sofian Hadi; Mutiarani Mutiarani; Aulia Rofika Hamid (English Teaching Journal : A Journal of English Literature, Language and Education, 2021)
This research aims to estimate and get to know more about self-confidence factors that may affect to English speaking proficiency level for Indonesian young learners. The researcher used a qualitative method. In this research, the primary data was collected by focusing on the aspects and points that the researcher wanted to observe about. The primary data was used as a model and framework of the conceptual learning and teaching through the speaking proficiency level. In addition, the main object for this research is about Indonesian young learners towards the English speaking proficiency level. The researcher hopes that there will be significant results based on the primary data that will show the impact of self-confidence to influence the speaking proficiency level by Indonesian young learners. Therefore, the final result of research will be meaningful for the future researches in the similar study. It goes the same to the teachers and students that participate in teaching and learning English.